2021
DOI: 10.3390/pathogens10020199
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequence Analysis of Phage-Resistant Listeria monocytogenes Serotype 1/2a Strains from Turkey Processing Plants

Abstract: Listeria monocytogenes is a Gram-positive bacterial pathogen and the causative agent of listeriosis, a severe foodborne infection. L. monocytogenes is notorious for its ability to persist in food processing environments (FPEs) via a variety of adaptive traits. Even though traits such as cold tolerance, biofilm formation and sanitizer resistance have been extensively investigated for their roles in persistence of L. monocytogenes in FPEs, much less is known about resistance to bacteriophages. Previous studies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…The ST321 strains from Plant A and Plant B harbored the T730 inlA PMSC, as also reported previously (Brown et al, 2021). ST321 isolates from a variety of sources have been previously reported to harbor inlA PMSCs, but in other locations.…”
Section: Premature Stop Codons In Inla Are Clonally Distributed and May Serve As Fpe-specific Markerssupporting
confidence: 84%
See 4 more Smart Citations
“…The ST321 strains from Plant A and Plant B harbored the T730 inlA PMSC, as also reported previously (Brown et al, 2021). ST321 isolates from a variety of sources have been previously reported to harbor inlA PMSCs, but in other locations.…”
Section: Premature Stop Codons In Inla Are Clonally Distributed and May Serve As Fpe-specific Markerssupporting
confidence: 84%
“…We found that inlA PMSCs were ST-specific and not randomly distributed among the sequenced FPE strains. Specifically, they were only encountered in seven of the nine strains of ST5 (serotype 1/2b; T635) and, as previously reported (Brown et al, 2021), in all six ST321 strains (serotype 1/2a; T730) (Supplementary Table 1; Figure 2).…”
Section: Premature Stop Codons In Inla Are Clonally Distributed and May Serve As Fpe-specific Markerssupporting
confidence: 77%
See 3 more Smart Citations